Implementasi Kebijakan Zonasi Wilayah Pesisir Dalam Mengendalikan Dampak Pariwisata: Studi Kasus Kawasan Wisata Bahari Mandeh, Sumatera Barat - Lisa Anisa; Juni Rahmad Hasibuan; Rico Irvanda; Eni Kamal; Widya Prarikeslan (Journal of Innovative and Creativity, 2025)
Indonesia as an archipelagic country faces complex challenges in managing coastal areas that have high economic value but are vulnerable to environmental degradation. This research analyzes the implementation of coastal zoning policies through the Coastal and Small Islands Zoning Plan (RZWP3K) based on West Sumatra Provincial Regulation Number 2 of 2018 in controlling tourism impacts in the Mandeh Marine Tourism Area. Using a normative-empirical gap analysis case study approach, this study examines the effectiveness of zoning policies in balancing economic utilization and coastal ecosystem conservation. The results show that the implementation of RZWP3K Regional Regulation in the Mandeh Area successfully created a legal framework that divides the area into five main zones: conservation zone (325 ha of mangroves), tourism zone (18,000 ha), capture fisheries zone, cultivation zone, and special mangrove zone with specific regulations in each zone. Integration with the Tourism Development Master Plan (RIPPAR) of Pesisir Selatan Regency 2026-2045 shows strong government commitment to realizing sustainable blue tourism, reflected in the 59% growth of accommodation infrastructure (56 hotels with 622 rooms in 2023) and tourism sector contribution to West Sumatra's GDP reaching 1.89%[1][2]. However, implementation faces challenges including delays due to revision of Regional Regulation Article 41(b) ratified in 2023, zoning conflicts between traditional fishing areas and tourism zones, and gaps between nagari government master plans and provincial regulatory provisions[3]. The research recommends harmonization of multi-level regulations, strengthening cross-sectoral coordination mechanisms, and optimizing technology-based monitoring systems for more effective implementation.